The IDENTIFICATION OF LANDSCAPE DESIGN ASPECTS ON THE AGRICULTURAL LAND OF THE KAMPOENG CE'DE FARMERS' GROUP IN MAROS DISTRICT - Gusti Hardyanti Musda; Asriyani Asriyani; Fitriani R (DEARSIP : Journal of Architecture and Civil, 2023)
Landscape design on agricultural land is an approach that is used to meet the needs of various types of activities in the agricultural sector, both users and commodities produced from agricultural land. This research aims to identify aspects of landscape design on the Kampoeng Ce'de agricultural land in Maros Regency, which will be used as a reference for formulating landscape concepts and designs. This research used descriptive qualitative research methods, data was collected by relying on direct observation techniques, interviewing the users, and utilizing relevant references. Then, the data was analyzed and synthesized to obtain the objectives of this research. The results of the research showed that there are three design aspects that need to be implemented to support activities on Kampoeng Ce'de agricultural land, which are Physical Aspects of the Architectural Landscape (materials, vegetation, circulation, accessibility, drainage systems and facilities), Agricultural System Aspects (horticulture cultivation techniques) and Supporting Technology Aspects (production of fish feed and agriculture fertilizer).